Contralateral Regional Recurrence in Lateralized or Paramedian Early-Stage Oral Cancer Undergoing Sentinel Lymph Node Biopsy—Comparison to a Historic Elective Neck Dissection Cohort - Mahieu, Rutger; den Toom, Inne J.; Boeve, Koos; Lobeek, Daphne; Bloemena, Elisabeth; Donswijk, Maarten L.; de Keizer, Bart; Klop, W. Martin C.; Leemans, C. René; Willems, Stefan M.; Takes, Robert P.; Witjes, Max J. H.; et al. (Frontiers in Oncology, 2021)
Introduction: Nowadays, two strategies are available for management of the clinically negative neck in early-stage (cT1-2N0) oral squamous cell carcinoma (OSCC): elective neck dissection (END) and sentinel lymph node biopsy (SLNB). SLNB stages both the ipsilateral as well as the contralateral neck in early-stage OSCC patients, whereas the contralateral neck is generally not addressed by END in early-stage OSCC not involving the midline. This study compares both incidence and hazard of contralateral regional recurrences (CRR) in those patients who underwent END or SLNB. Materials and Methods: A retrospective multicenter cohort study, including 816 lateralized or paramedian early-stage OSCC patients, staged by either unilateral or bilateral END (n=365) or SLNB (n=451). Results: The overall rate of contralateral nodal metastasis was 3.7% (30/816); the incidence of CRR was 2.5% (20/816). Patients who underwent END developed CRR during follow-up more often than those who underwent SLNB (3.9% vs. 1.3%; p=0.018). Moreover, END-patients had a higher hazard for developing CRR than SLNB-patients (HR=2.585; p=0.030). In addition, tumor depth-of-invasion was predictive for developing CRR (HR=1.922; p=0.009). Five-year disease-specific survival in patients with CRR was poor (42%) compared to patients in whom occult contralateral nodal metastases were detected by SLNB or bilateral END (88%), although not statistically different (p=0.066). Conclusion: Our data suggests that SLNB allows for better control of the contralateral clinically negative neck in patients with lateralized or paramedian early-stage OSCC, compared to END as performed in a clinical setting, which may provide a better prognosis for those with occult contralateral nodal metastasis.